2021
DOI: 10.1007/s12551-021-00829-2
|View full text |Cite
|
Sign up to set email alerts
|

Desmosomes: emerging pathways and non-canonical functions in cardiac arrhythmias and disease

Abstract: Desmosomes are critical adhesion structures in cardiomyocytes, with mutation/loss linked to the heritable cardiac disease, arrhythmogenic right ventricular cardiomyopathy (ARVC). Early studies revealed the ability of desmosomal protein loss to trigger ARVC disease features including structural remodeling, arrhythmias, and inflammation; however, the precise mechanisms contributing to diverse disease presentations are not fully understood. Recent mechanistic studies demonstrated the protein degradation component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Strikingly, we observed that ER/SR stress markers normalize in young adult mice with fully matured hearts and fully developed scar tissue (10–12 weeks) but increase again in older animals, especially in the right ventricular wall. We take this as evidence for deteriorating ER/SR function during chronic disease progression, which goes along with reduced ryanodine receptor 2 expression and was also described in conjunction with plakophilin 2 mutation [ 85 , 86 ]. In addition, reduced Serca2a expression was observed in right ventricles of Dsg2 MT mice during chronic AC progression [ 26 ], in the failing right ventricles of AC patients [ 26 ] and other cardiomyopathies [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, we observed that ER/SR stress markers normalize in young adult mice with fully matured hearts and fully developed scar tissue (10–12 weeks) but increase again in older animals, especially in the right ventricular wall. We take this as evidence for deteriorating ER/SR function during chronic disease progression, which goes along with reduced ryanodine receptor 2 expression and was also described in conjunction with plakophilin 2 mutation [ 85 , 86 ]. In addition, reduced Serca2a expression was observed in right ventricles of Dsg2 MT mice during chronic AC progression [ 26 ], in the failing right ventricles of AC patients [ 26 ] and other cardiomyopathies [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of murine cardiomyocytes, an increased frequency of spontaneous Ca 2+ release events was observed [ 89 , 90 ]. Some of these changes might be responsible for the susceptibility to arrhythmias characterizing the clinical phenotype of AC [ 86 , 95 , 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electrical remodeling, due to the destabilization of desmosomes, is a hallmark of ACM ( Rizzo et al, 2012 ; Stevens et al, 2022 ). Desmosomes are physically close to gap junctions, belonging to the same macromolecular complex ( Sato et al, 2011 ; Zhang J et al, 2021 ). Connexins are transmembrane proteins forming gap junctions enabling intercellular communication ( Desplantez et al, 2007 ; Dhein and Salameh, 2021 ).…”
Section: Established Molecular Mechanisms In Acmmentioning
confidence: 99%
“…Reduction of Connexin 43 (Cx43), a critical component of GJs, results in compromised electrical coupling and heterogeneous conduction between cardiomyocytes (Oxford et al, 2007;Rodriguez-Sinovas et al, 2021). These structural corruptions trigger cell death response, inflammatory infiltration, and metabolic perturbation that underpin clinical manifestations of electrical instability, cardiac structural deterioration, fibrofatty infiltration, and heart failure (Asatryan et al 2021;Austin et al, 2019;Cerrone et al, 2017;Chen et al, 2014;Dubash et al, 2016;Pérez-Hernández et al, 2022;Reichart et al, 2022;Song et al, 2020;Zhang et al, 2021).…”
Section: Mainmentioning
confidence: 99%